Ireland and the end of the British empire : the Republic and its role in the Cyprus emergency - O'Shea, Helen (Historian) (International library of historical studies, 2015)
"In 1949, Ireland left the Commonwealth and the British Empire began its long fragmentation. The relationship between the new Republic of Ireland and Britain was a complex one however, and the traditional assumption that the Republic would universally support self-determination overseas and object to 'imperialism' does not hold up to historical scrutiny. In reality, for economic and geopolitical reasons, the Republic of Ireland played an important role in supporting the Empire- demonstrated clearly in Ireland's active involvement in the Cyprus Emergency of the 1950s. As Helen O'Shea reveals, while the IRA formed immediate links with EOKA and the Cypriot rebels, the Irish government and the Irish Church supported the British line- which was to retain Cyprus as the Middle-Eastern base of the British Empire following the loss of Egypt. Ireland and the End of the British Empire challenges the received historiography of the period and constitutes a valuable addition to our understanding of Ireland and the British Empire."--Jacket